Bargielska bez wymówek - Koronkiewicz, Marta (Śląskie Studia Polonistyczne, 2014)
The author analyzes the critical reception of the works by Justyna Bargielska, pondering over mechanisms of defense from over-interpretation or critical misuse included in the poet’s books. Using the hypothesis of narrative sources in defense against accusation as a starting point, she researches Bargielska’s writing strategies, especially in the novel Małe lisy, in order to define the role of shame within. Bargielska’s characters refuse to be ashamed of things, which are generally considered shameful. The purpose of this work is to indicate that this phenomenon – called the “shamelessness strategy” – influences the form of text itself; what it allows for, and what it makes a necessity.